The Implementation of the Meaning of Ta‘zim Sya‘airillah in Digital Islamic Propagation: A Visual Analysis of Honoring Sacrificial Animals in YouTube Content - Muhammad Qudwatul Ibad; Fauzan Zenrif; Toriquddin Toriquddin (al-Afkar, Journal For Islamic Studies, 2026)
In the digital era, the propagation (syiar) of the Qurban sacrifice has transformed from physical spaces to the stage of YouTube, creating the "Sapi Sultan" (Sultan's Cow) phenomenon as a form of visual da’wah renegotiation that reflects modern Muslim identity. This study aims to conduct an in-depth analysis of the visual construction of animal glorification in digital content, specifically exploring how cinematographic elements interpret the theological criteria of istisman (fattening) and istihsan (beautifying). The methodology employed is Interpretative Qualitative Content Analysis of the deHakims YouTube channel, referenced against the authoritative text of Tafsir Al-Baghawi. The results indicate that the concept of istisman is implemented through low-angle cinematography and extreme tonnage narratives to create a "cinematography of piety," while istihsan is manifested through the visualization of animal welfare and exclusive care. However, a critical dialectic emerges where "Sultan" labeling and the emphasis on extravagant prices risk falling into the logic of spectacle religion, which can obscure the essence of internal piety into mere materialistic visual consumption. This research provides an important contribution to the development of visual analysis methodologies in contemporary Islamic studies by bridging classical texts with the reality of new media.